Safety of Cinnamon: An Umbrella Review of Meta-Analyses and Systematic Reviews of Randomized Clinical Trials - Gu, Dan-Tong; Tung, Tao-Hsin; Jiesisibieke, Zhu Liduzi; Chien, Ching-Wen; Liu, Wen-Yi (Frontiers in Pharmacology, 2022)
Purpose. Many evidence-based studies have indicated that cinnamon has therapeutic effects. However, it may not be totally safe and its adverse effects may be ignored. This umbrella review was conducted to elucidate the safety of cinnamon. Methods. Pertinent meta-analyses and systematic reviews of randomized controlled trials focused on cinnamon use in humans were identified by searching PubMed, EMBASE, and the Cochrane Library from inception to September 15, 2021. All meta-analyses and systematic reviews on the safety or adverse effects of cinnamon were considered. PRISMA 2020 was used as the standard of reporting (PRISMA registration ID is 286746). Results. We identified three meta-analysis and one systematic reviews for safe of cinnamon. The quality of the meta-analysis and systematic reviews was evaluated using Assessing the Methodological Quality of Systematic Reviews and rated as low in two (50%) instances and moderate in two (50%). There were no significant toxic/side effects between cinnamon group and placebo group regardless of dose and duration Conclusion. There is evidence to support that the use of cinnamon has no adverse reactions. Relatively, it can improve the health status of patients as an adjuvant treatment. Future studies need to explore better profile risk/protective factors for cinnamon use-related adverse effects, so that preventive approaches might be developed.